Perbaikan Ketahanan Tanaman Padi terhadap Penyakit Tungro - Ahmad Muliadi; I Nyoman Widiarta (Iptek Tanaman Pangan, 2017)
Tungro is an important rice disease caused by virus which is transmitted by green leafhopper (Nephotettix spp.) in semipersisten way. Resistant variety when available is considered as an effective control technique and is more environmental friendly. Rice breeding program to overcome the disease initially was aimed to produce green leafhopper resistant varieties. But a few years after releasing the resistant variety, it became susceptible because the green leafhopper could easily adapt to resistant varieties. There was an indication that the virus strains vary greatly. Broadening the genetic background of resistant varieties to green leafhopper and tungro viruses could be an alternative to build more durable resistance varieties. Rice breeding activities for resistance to tungro disease were to be continued to obtain more durable tungro resistant lines. Conventional breeding activities was considered justified, including the selection of tungro resistant lines applying pedigree or backcross methods, followed by observation of resistance genotypes to several strains of virus inoculums and to green leafhoppers. Selected resistant lines from the observation nurseries were followed by yield trials. Resistant lines that showed good yielding potential and good agronomic character would be proposed to be named as new tungro resistant varieties or as sources of tungro resistant genes. Varieties or genotypes that had been produced need to be tested for their resistance to green leafhopper colonies and to some virus strains from source of inoculum derived from endemic areas, to obtain resistance genotypes to be assembled as tungro resistant varieties, to be planted in the virus endemic areas.